2023
DOI: 10.1101/2023.09.12.557409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Rapid Anterior Auditory Processing Stream Through the Insulo-Parietal Auditory Field in the Rat

Maciej M. Jankowski,
Mousa Karayanni,
Mor Harpaz
et al.

Abstract: The insular cortex is believed to be involved in a wide range of auditory functions in the mammalian brain. We studied the organization and basic response properties of auditory neurons in insular cortex and adjacent areas by recording responses to sound stimuli in anesthetized rats. Auditory neurons were present in an insulo-parietal auditory field that spans the boundary between the posterior insula, particularly in the granular insular cortex and the ventral part of the secondary somatosensory cortex. Neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Several studies using animal models, including nonhuman primates, have also identified an auditory field in the posterior insula (Linke & Schwegler, 2000; Remedios et al, 2009; Rodgers et al, 2008). While this insular auditory field does receive input from primary and secondary auditory areas, it also receives direct parallel input from the auditory thalamus, evidenced in part by pure-tone responses in the insular auditory field sometimes having a lower response latency than the primary auditory cortex (Jankowski et al, 2023; Sawatari et al, 2011; Takemoto et al, 2014). Our own results parallel animal models, as we observed faster (or equivalently fast) responses to auditory playback stimuli in the posterior insula compared to primary (HG, PT) and higher order (STG, STS) auditory areas.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using animal models, including nonhuman primates, have also identified an auditory field in the posterior insula (Linke & Schwegler, 2000; Remedios et al, 2009; Rodgers et al, 2008). While this insular auditory field does receive input from primary and secondary auditory areas, it also receives direct parallel input from the auditory thalamus, evidenced in part by pure-tone responses in the insular auditory field sometimes having a lower response latency than the primary auditory cortex (Jankowski et al, 2023; Sawatari et al, 2011; Takemoto et al, 2014). Our own results parallel animal models, as we observed faster (or equivalently fast) responses to auditory playback stimuli in the posterior insula compared to primary (HG, PT) and higher order (STG, STS) auditory areas.…”
Section: Discussionmentioning
confidence: 99%